A rapid-assessment survey of the irrigation component of the Anuradhapura Dry-Zone Agricultural Project (ADZAP). - Ekanayake, R.; Navaratne, W.M.U.; Groenfeldt, D. (International Irrigation Management Institute, 1990)
The International Irrigation Management Institute (IIMI) in cooperation with the Department of Agrarian Services (DAS) conducted a study of 31 ADZAP tank schemes, focusing on the irrigation component of the project. The study was conducted during June-September 1988, and forms part of the Institute's ongoing research to document alternative strategies for assisting the minor irrigation sector. This report provides an overview of the study and its findings.